2018
DOI: 10.1111/1755-0998.12963
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcodes identify 99 per cent of apoid wasp species (Hymenoptera: Ampulicidae, Crabronidae, Sphecidae) from the Western Palearctic

Abstract: The apoid wasps have traditionally been regarded as a paraphyletic assemblage of four families (Ampulicidae, Crabronidae, Heterogynaidae and Sphecidae) that are closely related to the bees (Anthophila). The present study covers the three families of apoid wasps known to occur in Europe, that is, the Ampulicidae, Crabronidae and Sphecidae. DNA barcode sequences of 3,695 specimens of apoid wasps were analysed for the present study, including 21 specimens of Ampulicidae, 3,398 Crabronidae and 276 Sphecidae. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 19 publications
4
29
0
Order By: Relevance
“…Overall, most studies demonstrate a high degree of effectiveness of DNA barcoding for reliable genetic species delineation, assuming high standards of morphological determination of the samples tested. Thus, Schmid-Egger et al (2019) were able to differentiate 99% of the species via DNA barcode divergences in several Hymenopteran families. 92.5% of more than 3500 beetle species from Germany and neighbouring regions could be unambiguously identified with DNA barcodes (Hendrich et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, most studies demonstrate a high degree of effectiveness of DNA barcoding for reliable genetic species delineation, assuming high standards of morphological determination of the samples tested. Thus, Schmid-Egger et al (2019) were able to differentiate 99% of the species via DNA barcode divergences in several Hymenopteran families. 92.5% of more than 3500 beetle species from Germany and neighbouring regions could be unambiguously identified with DNA barcodes (Hendrich et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This local sequence database consists of the compiled data which are based on the DNA library with more than 23,000 barcoded German animal species assembled in two major DNA barcoding campaigns: “Barcoding Fauna Bavarica” (BFB, http://www.faunabavarica.de, Haszprunar, 2009) and “German Barcode of Life” project (GBOL, http://www.bolgermany.de, Geiger et al, 2010), with nearly 250,000 vouchers curated at the Zoological State Collection Munich, Germany (http://www.barcoding-zsm.de). Data releases have been published for all major arthropod groups, that is, Coleoptera (Hendrich et al, 2015; Raupach, Hannig, Moriniere, & Hendrich, 2016; Raupach, Hannig, Morinière, & Hendrich, 2018; Rulik et al, 2017), Diptera (Morinière et al, 2019), Ephemeroptera, Plecoptera, and Trichoptera (Morinière et al, 2017), Heteroptera (Havemann et al, 2018; Raupach et al, 2014), Hymenoptera (Schmid‐Egger et al, 2019; Schmidt, Schmid‐Egger, Morinière, Haszprunar, & Hebert, 2015; Schmidt et al, 2017), Lepidoptera (Hausmann, Haszprunar, & Hebert, 2011a; Hausmann, Haszprunar, Segerer, et al, 2011), Neuroptera (Morinière et al, 2014), Orthoptera (Hawlitschek et al, 2018), Araneae and Opiliones (Astrin et al, 2016), and Myriapoda (Spelda, Reip, Oliveira Biener, & Melzer, 2011; Wesener et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Currently, the DNA barcode library created by the ZSM researchers represents the second‐most comprehensive library of any nation. Previous studies have reported on barcoding results for Coleoptera (Hendrich et al, ; Raupach, Hannig, Moriniere, & Hendrich, ; Raupach, Hannig, Morinière, & Hendrich, ; Rulik et al, ), Ephemeroptera, Plecoptera and Trichoptera (Morinière et al, ), Heteroptera (Havemann et al, ; Raupach et al, ), Hymenoptera (Schmid‐Egger et al, ; Schmidt, Schmid‐Egger, Morinière, Haszprunar, & Hebert, ; Schmidt et al, ), Lepidoptera (Hausmann, Haszprunar, & Hebert, ; Hausmann, Haszprunar, Segerer, et al, ), Neuroptera (Morinière et al, ), Orthoptera (Hawlitschek et al, ), Araneae and Opiliones (Astrin et al, ), and Myriapoda (Spelda, Reip, Oliveira Biener, & Melzer, ; Wesener et al, ). Concerning DNA barcoding studies performed for Diptera, no comprehensive study encompassing this entire highly diverse order has been published, but data have been used to revise smaller units thereof: for example, for Calliphoridae (Jordaens et al, ; Nelson, Wallman, & Dowton, ; Reibe, Schmitz, & Madea, ), Ceratopogonidae (Stur & Borkent, ), Chironomidae (Carew, Pettigrove, Cox, & Hoffmann, ; Carew, Pettigrove, & Hoffmann, ; Cranston et al, ; Ekrem, Stur, & Hebert, ; Ekrem, Willassen, & Stur, ; Montagna, Mereghetti, Lencioni, & Rossaro, ; Pfenninger, Nowak, Kley, Steinke, & Streit, ; Sinclair & Gresens, ; Stur & Ekrem, ), Culicidae (Ashfaq et al, ; Cywinska, Hunter, & Hebert, ; Kumar, Rajavel, Natarajan, & Jambulingam, ; Versteirt et al, ; Wang et al, ), Hybotidae (Nagy, Sonet, Mortelmans, Vandewynkel, & Grootaert, ), Muscidae (Renaud, Savage, & Adamowicz, ), Psychodidae (Gutiérrez, Vivero, Vélez, Porter, & Uribe, ; Krüger, Strüven, Post, & Faulde, ; Kumar, Srinivasan, & Jambulingam, ; Nzelu et al, ), Sciaridae (Eiseman, Heller, & Rulik, ; Heller, Köhler, Menzel, Olsen, & Gammelo, ; Heller & Rulik, ; Latibari, Moravvej, Heller, Rulik, &...…”
Section: Introductionmentioning
confidence: 99%